Physical determinants of vault performance and their age-related differences across male junior and elite top-level gymnasts - Schärer, C.; Haller. N.; Taube, W.; Hübner, K. (PLOS ONE, 2019)
In order to perform difficult vaults in artistic gymnastics, athletes have to achieve high run-up speeds within the limited run-up distance (25m). However, the physical parameters that contribute to a high run-up speed and their age-related differences remain elusive. Hence, the aim of this study was 1) to investigate interrelations between difficulty value (D-score) and run-up kinematics of Handspring/Tsukahara and Yurchenko vaults as well as lower body power (25m-sprint, explosive and reactive strength) and 2) to explore age-related differences of these parameters across junior and elite gymnasts performing Handspring/Tsukahara vaults. For this purpose, the data (of the above mentioned parameters) of 47 top-level male elite and junior gymnasts aged 14.3 to 28.3 of performance testing, gathered over three years, were analysed. We found that D-score of Handspring/Tsukahara (n = 33) was strongly correlated with run-up speed (r = 0.79; p < 0.01). Further, 25m sprint speed (r = 0.85; p < 0.01) was significantly associated with run-up speed of Handspring/Tsukahara vaults. There were no significant relationships with the D-score of Yurchenko (n = 14). Looking at the age-related differences of Handspring/Tsukahara, D-score increased significantly from junior to elite level (+11.6%; p < 0.01). The comparison between consecutive agegroups revealed that the U19 group had higher run-up speeds, step lengths, body weights and heights than the U17 group, while the U21 group achieved significantly higher speeds (run-up, 25m-sprint) and explosive strength than the U19 group. We concluded 1) that the optimization of important physical determinants may increase the potential to perform more difficult Handspring/Tsukahara vaults and 2) that first growth and maturation and later improvements of lower body power led to higher run-up speeds of Handspring/Tsukahara in the subsequent age-group. Therefore, based on performance testing of the lower limbs, training recommendations should be given specifically to the requirements of the competition vault.